Prevalence, risk factors and transmission of viral nervous necrosis in a hatchery producing hybrid grouper [♂ Epinephelus lanceolatus (Bloch, 1790) × ♀ Epinephelus fuscoguttatus (Forsskål, 1775)] fry - Ahmad, Atirah Khairiah (2018)
Fisheries and aquaculture are essential source of food, nutrition and also earnings for hundreds of millions of people around the world. One of the most cultured marine fish all around the world was grouper. Grouper is one of the high value and demanded cultured marine fish especially in the Southeast Asia countries. However, the supply of groupers from aquaculture is often limited due to diseases, mainly from Betanodavirus. The diseases caused by these viruses are commonly known as Viral Nervous Necrosis (VNN). VNN has been recognized to give tremendous mass mortality of fish all around the world and this virus is primarily affecting the larval and juvenile stages of fish. Therefore, this study investigates the prevalence, risk factors and transmission of viral nervous necrosis in a hatchery producing hybrid grouper [♂ Epinephelus lanceolatus (Bloch, 1790) × ♀ Epinephelus fuscoguttatus (Forsskål, 1775)] fry. The experiment was conducted in a marine fish hatchery located in Terengganu, Malaysia. Artificial breeding of hybrid groupers fry was conducted at monthly interval for 12 months from March 2016 to April 2017. A total of 61 broodstocks with 28 male giant groupers (E. lanceolatus), and 33 female tiger groupers (E. fuscoguttatus) were used and sampled in this experiment. In general, the number of broodstocks sampling for each month were between one to three broodstocks for giant grouper (GG), while for tiger grouper (TG), it was between two to four broodstocks. Three artificial breeding attempts with different VNN status of broodstocks, which were : 1) VNNpositive GG × VNN-positive TG (GG+ × TG+); 2) VNN-positive GG × VNN-negative TG (GG+ × TG-); and 3) VNN-negative GG × VNN-negative TG (GG- × TG-) were conducted. Then, after fertilization, the fry was observed for VNN status at 5, 10, 20, 30, 40, 60, 90 and 120 days’ post hatching, while the water quality during the study period were recorded. The detected VNN were proceed for VNN transmission study and molecular characterization analysis. Then, the sequences obtained in this study were compared with those of the other typical VNN isolates available in the GenBank/EMBL nucleotide database. The phylogenetic tree was constructed by neighbor-joining analysis with the MEGA7 program. The prevalence of VNN in broodstocks throughout 12 months of sampling periods showed low detection of VNN. Viral Nervous Necrosis only detected in April 2016 with a percentage of 50% for GG and 33.33% for TG broodstocks. There were significant correlations between the presence of VNN in GG, TG and hybrid grouper (HG) fry in selected water quality parameters. Iron and ammonia consistently showed significant positive and strong relationship with the presence of VNN in GG, TG and produced HG fry. Viral Nervous Necrosis transmission study and molecular characterization analysis suggested possible horizontal and vertical transmission of VNN between the groupers in this hatchery. The VNN might be transmitted between broodstock to broodstock, fry to fry and broodstocks to fry or vice versa, and circulated inside the hatchery culture system. In addition, detected VNN strains in this study were closely related between each other and distinctively grouped from other VNN strains, including from East Malaysia. Therefore, this study provides significant information for control and prevention of VNN to farmers in this country that producing HG fry at hatchery level.